THE IMPACT OF LIQUIDITY ON FINANCIAL DISTRESS - Angela Irena; Thomson Sitompul (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
This research conducted using 7 year-period data to examine the financial performance fluctuation before and after pandemic COVID-19. The purpose is to analyze the Impact of Liquidity towards Financial Distress with Firm Size as the Moderating Variable. The independent variable used in this research is Liquidity measured by Current Ratio. The dependent variable is Financial Distress which is measured by using Altman Z-Score formula. In addition, moderating variable Firm Size is measured by Ln multiply to Total Assets. By having the secondary data from infrastructure sector companies listed on the IDX in 2017-2023 and using purposive sampling method, 43 infrastructure companies are chosen as the samples from total of 65 companies. The data analysis in this research is using descriptive statistics, including minimum, maximum, mean and standard deviation. Then, multiple linear regression with classical assumption tests was used in this research. With that, data is processed through SPSS Statistics 25. The result of this study shows that Liquidity has significant impact towards Financial Distress. However, Firm Size is not able to moderate the relationship between Liquidity and Financial Distress since Liquidity has no significant impact towards Financial Distress through Firm Size as its moderating variable.